Anti-serum with anti-autoantibody activity decreases autoantibody-positive B lymphocytes and type 1 diabetes of female NOD mice. (2nd January 2016) - Luan, Lijuan; Xue, Rong; Lu, Chao; Cui, Anfeng; Hou, Yanqiang; Quan, Jing; Xiang, Meng; Wang, Xinhong; Yuan, Wenjun; Sun, Ning; Meng, Dan; Chen, Sifeng
Abstract: Type 1 diabetes mellitus (T1DM) is an autoimmune disease characterized by an autoimmune-mediated loss of insulin secreting β-cells. Each B lymphocyte clone that escapes immune tolerance produces a specific antibody. No specific treatment against autoantibodies is available for autoimmune diseases. We have developed a strategy to produce an antiserum against autoantibodies for the treatment of T1DM. Non-obese diabetic (NOD) but not Balb/c mouse serum contains autoantibodies. Antisera were produced by immunizing Balb/c mice with affinity-purified IgG from NOD or BALB/c mice along with the immune adjuvant (hereafter, NIgG or BIgG, respectively). A bolus administration of NIgG significantly reduced serum autoantibodies, autoantibody-positive B lymphocytes in the spleens of NOD mice, mortality and morbidity of diabetes, blood glucose and islet immune infiltration, whereas it increased islet mass in NOD mice for at least 26 weeks. NIgG antiserum treatment has no significant effect on CD3 +, CD4 + or CD8 + T cells and B220 + or CD19 + B cells. BIgG also imparted a moderate therapeutic effect, although it was considerably lower than that of NIgG. NIgG did not cross-react with allogeneic serum. NIgG showed no effect on Balb/c mice. The results show the feasibility of producing antiserum against autoantibodies to prevent and treat autoimmune-induced T1DM with a single bolus administration.